Analysis of Document Management Systems Electronic Secret News - Arsih, Peni (Sekolah Tinggi Teknologi Adisutjipto, 2018)
The process of news administration from the ranks in the area, entered through a fax machine coded in the password room which was then distributed to the destination work unit by courier / caraka. To ensure the confidentiality of news documents, an encryption process is performed using the Blowfish algorithm, this algorithm is chosen because it has the fastest form of other block cipher algorithms (Salama, Elminaam, Mohamed, Kader, & Hadhoud, 2010). Then to guarantee the integrity of the archive, the Whirlpool hash function is used, this algorithm is able to produce hash values that have an output length of 512 bits but with a faster time than the NIST recommendation algorithm, SHA-512 (Cryptopp, 2009), besides Whirlpool is a standard hash function ISO / IEC 10118-3: 2003. For the legalization process and ensuring the authenticity of the news can be fulfilled by the RSA Digital Signature algorithm, the algorithm is chosen because it complies with the NIST FIPS 186-4 standard. The news management application that will be designed is also adjusted to the minimum electronic system requirements in accordance with Law Number 11 of 2008, which can protect the integrity, authenticity, confidentiality and accessibility of electronic information. This research will produce an application that is capable of managing web-based electronic confidential news documents. The application can also guarantee the confidentiality, integrity, and authenticity of managed news documents. It is expected that with this application, it can meet management needs